2019
DOI: 10.1002/ejic.201801433
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of the Frontier Orbital Character in Co2+/3+ Complexes with Triarylamine Substituted Terpyridine Ligands

Abstract: Tara‐decorated terpyridines 1–3 and their 1:2 Co2+ [Co(L)2](ClO4)2 (L = 1–3) and Co3+ complexes [Co(L)2](ClO4)2(SbCl6) (L = 1,3) are reported. The solid‐state complex metrics of [Co(3)2]2+ and [Co(1)2]3+ indicate an assignment as spin‐quartet Co2+ or spin‐singlet Co3+, which is in accord with DFT and 1H NMR studies. Vis‐NIR spectra of 1[Co3+(L)2]3+ show characteristic Tara→Co3+ charge‐transfer bands, giving no direct indication of L‐based oxidation events, irrespective of the solvent. Theoretical studies revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…Without affecting the absolute orbital energies much, the donor levels of TTF in 4 intercalate the block of largely metal-borne occupied MOs which characterize REF. Similar observations have been recently made in a N 6 coordinate cobalt­(II) triarylamine diade, where the electrophores were found electronically uncoupled . With respect to the redox of 4 , it is important to note that it is clearly a metal-localized orbital which features at highest energy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Without affecting the absolute orbital energies much, the donor levels of TTF in 4 intercalate the block of largely metal-borne occupied MOs which characterize REF. Similar observations have been recently made in a N 6 coordinate cobalt­(II) triarylamine diade, where the electrophores were found electronically uncoupled . With respect to the redox of 4 , it is important to note that it is clearly a metal-localized orbital which features at highest energy.…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations have been recently made in a N 6 coordinate cobalt(II) triarylamine diade, where the electrophores were found electronically uncoupled. 62 With respect to the redox of 4, it is important to note that it is clearly a metallocalized orbital which features at highest energy. This fact once more points out the similarity among 4 and REF and therefore suggests metal centered oxidation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[33][34][35] To date, 6,6″ modified bis terpyridine complexes have been rarely reported. [36][37][38] Constable et al, reported the homoleptic Ru and Fe complexes, in which 6,6″-position groups weaken the ligand field of Fe complex, resulting in distinct high-spin state. 38 In our opinion, 6,6″ substituted terpyridine complexes have two merits: (1) the groups in the 6,6″ position are closer to the coordination center than that of other sites, which will ensure adjustable steric hindrance and coordination configuration by selecting proper substituents, and this is very important for the properties of transition metal complexes; (2) the head-to-tail coordination mode may be beneficial for achieving intramolecular electron interactions, such as through-space charge-transfer (TSCT).…”
Section: Introductionmentioning
confidence: 99%